A Delphi Study on the Management of Female Infertility by Homeopaths in South Africa - Robyn Anderson; Janice Pellow; Tebogo Tsele-Tebakang; Elizabeth Solomon (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
ackground: Infertility affects millions of people worldwide and has a negative social and psychological impact on the lives of infertile couples. Homeopathy offers an alternative treatment option for female infertility; however, there is currently no research describing how homeopaths manage this condition in their practice.